Seeing further the story of science, discovery, and the genius of the Royal Society - Bryson, Bill; Turney, Jon (William Morrow an imprint of HarperCollins Publishers, 2010)
As editor of "Seeing Further," Bryson has rounded up an extraordinary roster of scientists who write and writers who know science in order to celebrate 350 years of the Royal Society, Britain's scientific national academy. The contributors include Margaret Atwood, Steve Jones, Richard Dawkins, James Gleick, Richard Holmes, and Neal Stephenson, among many others, on subjects ranging from metaphysics to nuclear physics, from the threatened endtimes of flu and climate change to our evolving ideas about the nature of time itself, from the hidden mathematics that rule the universe to the cosmological principle that guides "Star Trek."